The Unemployed with Jobs and without Jobs - Robert E. Hall; Marianna Kudlyak (Institute of Labor Economics (IZA), 2022)
Potential workers are classified as unemployed if they seek work but are not working. The unemployed population contains two groups—those with jobs and those without jobs. Those with jobs are on furlough or temporary layoff. This group expanded tremendously in April 2020, at the trough of the pandemic recession. They wait out periods of non-work with the understanding that their jobs still exist and that they will be recalled. We show that the resulting temporary-layoff unemployment mostly dissipated by the end of 2020. Potential workers without jobs constitute what we call jobless unemployment. Shocks that elevate jobless unemployment have much more persistent effects. Historical major adverse shocks, such as the financial crisis in 2008, created mostly jobless unemployment and consequently caused extended periods of elevated unemployment. Jobless unemployment reached its pandemic peak in November 2020, at 4.9%, modest by historical standards, and has declined at a faster-than-historical pace since.
Keywords: E32; J63; J64; 330; business cycle; recovery; unemployment; recession; layoffs; temporary layoff; recall; COVID-19